Comparing the Incidence of Index Level Fusion Following Minimally Invasive Versus Open Lumbar Microdiscectomy. Issue 1 (February 2018) - McAnany, Steven J.; Overley, Samuel C.; Anwar, Muhammad A.; Cutler, Holt S.; Guzman, Javier Z.; Kim, Jun S.; Merrill, Robert K.; Cho, Samuel K.; Hecht, Andrew C.; Qureshi, Sheeraz A.
Study Design: Retrospective cohort study. Objectives: To determine the incidence of index level fusion following open or minimally invasive lumbar microdiscectomy. Methods: We conducted a retrospective review of 174 patients with a symptomatic single-level lumbar herniated nucleus pulposus who underwent microdiscectomy via a mini-open approach (MIS; 39) or through a minimally invasive dilator tube (135). Outcomes of interest included revision microdiscectomy and the ultimate need for index level fusion. Continuous variables were analyzed with independent sample t test, and χ 2 analysis was used for categorical data. A multivariate regression analysis was performed to identify predictive factors for patients that required index level fusion after lumbar microdiscectomy. Results: There was no difference in patient demographics in the open and MIS groups aside from length of follow-up (60.4 vs 40.03 months, P < .0001) and body mass index (24.72 vs 27.21, P = .03). The rate of revision microdiscectomy was not statistically significant between open and MIS approaches (10.3% vs 10.4%, P = .90). The rate of patients who ultimately required index level fusion approached significance, but was not statistically different between open and MIS approaches (10.3% vs 4.4%, P = .17). Multivariate regression analysis indicated that the need for eventual index level fusion after lumbar microdiscectomy was statistically predicted in smokers and those patients who underwent revision microdiscectomy ( P < .05) in both open and MIS groups. Conclusions: Our results suggest a low likelihood of patients ultimately requiring fusion following microdiscectomy with predictors including smoking status and a history of revision microdiscectomy.